Indigenous knowledge, beliefs, and practices in rice farming of people in Cuyo Island, Palawan - Acero, Agnes B. (2005)
This study was conducted to determine the indigenous knowledge, beliefs, and practices in rice farming of people in Cuyo Island, Palawan. It also aims to find out the indigenous knowledge, beliefs and practices in planting, harvesting, storing, processing, and selling rice products.